Anti-ovary antibodies after attempts at human in vitro fertilization induced by follicular puncture rather than hormonal stimulation - B. Gobert; P. Barbarino-Monnier; F. Guillet-May; M. C. Béné; G. C. Faure (Reproduction, 1992)
Summary. Anti-ovary antibodies (AOA) have been detected in serum samples of women undergoing in vitro fertilization (IVF). High concentrations of these antibodies have been found in women who have had several IVF attempts and they appear to correlate with reduced chances of pregnancy. In this paper, AOA were assayed sequentially in a series of 140 IVF candidates to investigate the respective roles of hormonal stimulation and follicular puncture in inducing the autoimmune response. Serum was obtained 8 days after the beginning of ovarian human menopausal gonadotrophin (hMG) stimulation, then 15 days after follicular puncture. Significantly higher concentrations of IgG (P < 0·0001) AOA were observed in the second series of samples than in the first, suggesting that ovarian trauma and not hormonal stimulation is responsible for triggering antibody production. In the whole group, there was a negative correlation between IgM levels after puncture and oocyte numbers (P < 0·05). Among 'immune-responder' women, the concentrations of IgA AOA (P = 0·01) in the first sample, and of IgG (P = 0·01) or IgA AOA (P < 0·05) in the second, correlated with fewer oocytes after stimulation. There was no variation in the mean concentrations of AOA in women who achieved pregnancy. Keywords: human; autoantibodies; ovary; in vitro fertilization